2022
DOI: 10.1142/s0217979222501703
|View full text |Cite
|
Sign up to set email alerts
|

Heat transfer analysis in three-dimensional unsteady magnetic fluid flow of water-based ternary hybrid nanofluid conveying three various shaped nanoparticles: A comparative study

Abstract: The heat transport analysis in the three-dimensional unsteady flow of non-Newtonian nanofluid is studied in this research communication. Comparison of water-based ternary hybrid nanofluid conveying three various shaped nanoparticles (titanium spherical-carbon nanotube (CNT) cylindrical-graphene platelet) and Zinc Oxide-Society of Automotive Engineers 50 nanolubricant (ZnO-SAE50Nanolubricant) is emphasized with two different models. Also, this paper is mainly focused on an electrically non-conducting and incomp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…The investigations on MHD heat transportation in a variety of physical systems has achieved prominent attention due to its substantial industrial and medicinal applications. 3743 Some of the most important studies discussing the effects of MHD on flow of nanofluids over different geometries can be found in Giri et al 4447 and Das et al 48…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The investigations on MHD heat transportation in a variety of physical systems has achieved prominent attention due to its substantial industrial and medicinal applications. 3743 Some of the most important studies discussing the effects of MHD on flow of nanofluids over different geometries can be found in Giri et al 4447 and Das et al 48…”
Section: Introductionmentioning
confidence: 99%
“…The investigations on MHD heat transportation in a variety of physical systems has achieved prominent attention due to its substantial industrial and medicinal applications. [37][38][39][40][41][42][43] Some of the most important studies discussing the effects of MHD on flow of nanofluids over different geometries can be found in Giri et al 44-47 and Das et al 48 For the situations, such as polymer array, a few suspensions, different emulsion types and froths (liquid behaves as a particle) where the partial slip is the most appropriate BC, it is true that no slip BC is not quite sufficient. Numerous researchers are convinced to conduct research into a few fields related to the partial slip condition because of the significant opportunities in the polymer and electrochemical industries.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Gowda et al 9 demonstrated laminar flow of a magnetic liquid induced by a stretching sheet under the influence of thermal radiation and Cattaneo-Christov heat flux while comparatively examining the flow dynamics regarding propylene glycol-water fusion + paraffin wax nanofluid and ZnO + SAE 50 nanolubricant, as a result of which they concluded the latter showed optimal performance contrary to the earlier one. Further improvements were illustrated by Kumar et al 10 when the researchers considered water-based ternary hybrid nanofluid carrying three distinct morphological nanoadditives of Ti (spherical)+CNTs (cylindrical)+ graphene (platelets) and compared it with the performance of ZnO + SAE 50 nanolubricant. Besides Newtonian fluids, many mathematical models describing non-Newtonian fluidic mediums have been considered as base fluids for forming hybrid nanofluids.…”
Section: Introductionmentioning
confidence: 99%
“…Convective heat transport with attached Casson fluid is studied by Jyothi et al [31]. The impact of exponential form of internal heat generation on water-based ternary hybrid nanofluid flow is disclosed by [32][33][34][35][36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%